Una revisión del estado actual de los envases para la industria alimentaria (2018)
The food industry is responsible for transforming products derived from agriculture and livestock into products suitable for the consumer’s consumption. In this process of transformation, the packaging industry plays a fundamental role in the conservation, distribution and sale of the product. The objective of this work is to demonstrate the importance of the new generation of containers, analyzing for this the origin of traditional food packaging and evolution towards active and intelligent packaging. In particular, for the food products, the general concepts of the so-called active packaging and smart packaging are presented, which respond to the new demands of the consumer. Finally, the new trends are studied.